IMPLEMENTASI PENDEKATAN DEEP LEARNING DALAM PEMBELAJARAN MENULIS PUISI: STUDI KASUS DI KELAS-11 SMK NEGERI 2 SURAKARTA - Gita Hapsari; Andayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning to write poetry at the Vocational High School (SMK) level still faces various problems, such as low student interest, limited creativity, and the use of learning methods that tend to be conventional and oriented towards the final result. These conditions cause students to be less actively involved and unable to express ideas in depth. This study aims to describe the planning, implementation, as well as obstacles and solutions in implementing the deep learning approach in poetry writing learning in grade 11 of SMK Negeri 2 Surakarta. This study uses a qualitative approach with a case study type. Data were obtained through observation, interviews, and document analysis with validity techniques using triangulation of sources, methods, and theories. The results of the study indicate that the implementation of the deep learning approach can increase student engagement through exploration, reflection, and contextual activities. Students become more active, creative, and are able to increase personal experiences in writing poetry. Despite obstacles such as limited time and student readiness, the solutions implemented by teachers can optimize the learning process.